An open AlgoWiki encyclopedia of algorithmic features: from mobile to extreme scale - Voevodin, Vl.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2015)
One of the fundamental problems of high performance computing consists in the necessity of a careful matching between the algorithmic structure of parallel programs and the features of a particular computer architecture. The performance capabilities of modern computers are significant; however, the computer’s efficiency drastically decreases if such a matching is not achieved even in one of the stages during the process of solving a problem. The AlgoWiki project is based on the fact that the features of algorithms by themselves are not dependent on computing systems. In other words, a detailed description of machine-independent properties of an algorithm should be done only once; after that, this description can be used many times when implementing this algorithm on various hardware/software environments. Also of importance of this project is its machine-dependent part devoted to the description of algorithmic implementation peculiarities with consideration of particular hardware/software platforms. The main result of this project is an open AlgoWiki encyclopedia covering the properties of algorithms and the peculiarities of their implementation on various computing systems. The knowledge of how to reveal, describe, analyze, and interpret the properties of algorithms will become of significant importance in a few years. This conclusion is valid for future exaflop supercomputers and for other computing platforms: from server to mobile devices.